Triple-layer remote phosphor structure: a selection of the higher color quality and lumen efficiency for WLEDs - Phan Xuan Le; Le Hung Tien (Institute of Advanced Engineering and Science, 2021)
To enhance color quality of glass-based phosphor-converted white light-emitting diodes (pc-WLEDs) with multi-layer remote phosphor layer structures, two phosphors, green CdS:In and red ZnS:Te,Mn, are integrated into the glass matrix and applied to the dual-layer and triple-layer WLED packages. The attained results were examined with Mie-scattering theory and Lambert-Beer law. The dual-layer showed significant enhancement in color rendering index (CRI), in the range of approximate 80-90. Meanwhile, CRI in the triple-layer was lower and stayed around 66. In terms of color quality scale (CQS), a more overall color evaluating index, triple-layer structure helps the glass-based WLED achieve higher value than the dual-layer. The triple-layer is also beneficial to the luminous efficacy, according to the experimented results. Thus, the triple-layer structure can be used to strengthen the benefit of the glass matrix used in WLED products.